Kualitas Pelayanan Publik Transportasi Kereta Rel Listrik di Stasiun Kota Bekasi - Nizar Azi Ferdiandi; Asep Nurwanda; Asep Nurdin Rosihan Anwar (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
The city of Bekasi has very rapid development, which is different compared to the surrounding areas and cities. The Bekasi City Government plays a very important role in the progress of public transportation, one of which is the KRL. Because the city of Bekasi itself is one of the centers of economic growth and activities in various regions/cities. With the population increasing every year, the community really needs practical, fast and affordable modes of transportation for daily use to avoid traffic jams. However, this KRL still has many problems related to services that are not yet optimal. This research is motivated by how the Electric Rail Public Transportation Service by PT. Kereta Commuter Indonesia Bekasi City Branch, this research uses a qualitative approach with a descriptive method. This research aims to find out how the Electric Railway Public Transportation Service by PT. Indonesian Commuter Train, Bekasi City Branch, Data sources used include secondary data and primary data. Data collection techniques in this research are document study, interviews and observation. The Bekasi city government has provided electric rail public transportation facilities, there are several service evaluation factors that must be carried out. Namely safety and comfort which should be adequate facilities for public transportation users.